The man who started the Civil War : James Chesnut, honor, and emotion in the American South - Koivusalo, Anna (University of South Carolina Press, 2022)
"In the pre-dawn hours of April 12, 1861 James Chesnut Jr. hand-delivered a message to Major Robert Anderson, the U.S. Army commander at Fort Sumter. Chesnut informed Anderson that Confederate guns would commence the bombardment of the fort within the hour. Chesnut then piloted a small skiff across the dark waters of Charleston Harbor and delivered a fateful order to the batteries stationed on James Island. They were to open fire on Fort Sumter. Chesnut had just ordered the first shots of the Civil War. In 'The Man Who Started the Civil War' historian Anna Koivusalo offers the first full-length biography of South Carolina soldier and politician James Chesnut Jr. Prior to the Civil War, Chesnut served in both the South Carolina House and Senate before being appointed as a US Senator from South Carolina in 1858. Chesnut resigned his position in the US Senate shortly after the election of Abraham Lincoln in 1860. During the Civil War he served on the staff of Confederate President Jefferson Davis and was later appointed brigadier general of South Carolina reserve troops. Today he is probably best remembered as the husband of memoirist Mary Boykin Chesnut, whose wildly popular book 'A Diary from Dixie' remains an important source for understanding the Civil War era. In fact, Mary Chesnut had intended to write a biography of her husband, but she died before she was able. Koivusalo not only finishes that work, but in so doing deepens and expands our understanding of antebellum southern society, the coming of the Civil War, and its aftermath. 'The Man Who Started the Civil War' is more than just a biography of Chesnut, it is an emotional history of the man and his society. It deftly weaves together the history of emotions and the study of southern honor, showing how honor served as a dynamic means of creating, refining, and expressing honorable emotions. Understanding that the emotional worlds of elite white southerners like James Chesnut is crucial to understanding the coming of the Civil War. Focusing on the role of emotion in the coming of the Civil War does not ignore the central role of slavery. Both honor culture and honorable emotional expression were predicated on the existence of slavery. Without enslavement, there could be no mastery for men like Chesnut. It was one of the things they feared most. Honor and emotion were also central to the proslavery argument and Koivusalo shows how Chesnut and others used emotional expression to justify slavery and thus preserve the wealth and privilege of the upper class. But understanding the how and when of the Civil War requires more than just acknowledging the role of slavery. Koivusalo helps readers to understand why political solutions came to be seen as untenable and why the war came in 1861 rather than earlier or later. These are questions that have long vexed historians. Because Chesnut's life spanned the antebellum and postbellum years, Koivusalo is also able to explore how the war shifted and shattered pre-war conceptions of honor and emotional expression. The latter portions of the book examine Chesnuts' attempts, largely unsuccessful, to navigate that postwar world"--